Clinical researchGlucose metabolism in conventionally treated patients with b-thalassaemia major assessed with oral glucose tolerance test - Christoforidis, Athanasios; Perifanis, Vassilios; Tsatra, Ioanna; Vlachaki, Efthimia; Athanassiou-Metaxa, Miranda (Archives of Medical Science, 2008)
Introduction: The aim of the study was to assess prevalence and risk factors of glucose intolerance in thalassaemic patients, optimally treated since early in life. In addition, the evolution of glycaemic indices (b-cell function, insulin resistance and insulin sensitivity) with aging and their correlation with several parameters were investigated. Material and methods: Seventy-four patients (35 M and 39 F) with b-thalassaemia major (mean age: 20.52±5.12), treated with regular blood transfusions and adequate chelation treatment, were enrolled in the study. They were all assessed with oral glucose tolerance test, whereas data regarding serum ferritin concentrations, hepatitis C status, splenectomy, and body mass index (BMI) were available. Results: Results showed a prevalence of 12.2 and 5.4% for impaired glucose tolerance (IGT) and diabetes mellitus, respectively. Ferritin concentrations were significantly increased in patients with IGT, whereas there was no clear association between hepatitis C virus infection, splenectomy or BMI and the development of glucose intolerance. A significant decrease in b-cell function index was noted in diabetic patients in comparison to patients with both IGT and normal glucose metabolism. A deterioration of b-cell function was observed with ageing, although it was not statistically significant. Insulin sensitivity index was significantly decreased in thalassaemic patients with IGT. Conclusions: The results indicate that glucose intolerance is still frequent among thalassaemic patients, especially in their third decade of life. Moreover, our data suggest that glucose intolerance in b-thalassaemia major is characterized by progressive deterioration of insulin secretory capacity with a concomitant reduction in insulin sensitivity.